Executive poverty experience and innovation performance: A study of moderating effects and influencing mechanism - Jia, Ximeng; Wang, Tao; Chen, Chen (Frontiers in Psychology, 2022)
This paper analyzes the impact mechanism of executive poverty experience on innovation performance from the two logics of “innate endowment” and “endogenous power.” It then explores the moderating role of executive characteristics, firm nature, and market competition from the perspective of heterogeneity, and finally proves the influence mechanism. Using the data of Chinese A-share listed companies from 2012 to 2020, the empirical results show that executives’ poverty experience improves corporate innovation performance. Further studies find that female executives with poverty experience have a more significant impact on innovation performance. Additionally, state-owned enterprises (SOEs) weaken the positive effects of executives with poverty experiences on innovation performance. The impact of executive poverty experience on innovation performance is more significant in fierce market competition. The mediating result suggests that executive poverty experience improves innovation performance partly by inhibiting R&D manipulation. The findings remain valid through Propensity Score Matching (PSM) tests, the Heckman two-stage, and alternative indicator measures. Using the early life poverty experience of executives, this study promotes research on the factors influencing corporate innovation. It also provides empirical evidence for improving corporate innovation performance through a study of moderating effects and influencing mechanisms.